The welfare effects of health-based food tax policy - Kaisa Kotakorpi; Tommi Härkänen; Pirjoq Pietinen; Heli Reinivuo; Ilpo Suoniemi; Jukka Pirttilä (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper examines the effects of health-oriented food tax reforms on the distribution of tax payments, food demand and health outcomes. Unlike earlier work, we also take into account the uncertainty related to both demand estimation and health estimates and report the confidence intervals for the overall health effects instead of only point estimates. A sugar tax of 1 exteuro / kg reduces the incidence of type 2 diabetes on average by 13% and it also leads to a reduction in coronary heart disease. The health effects appear to be most pronounced for low-income individuals, and the reforms may therefore reduce health inequality. This effect undermines the traditional regressivity argument against the heavy taxation of unhealthy food.
Keywords: H20; I14; I18; 330; sin taxes; food taxation; tax incidence; commodity demand; obesity; diabetes; coronary heart disease; bootstrapping